Anatomy of the Cranial Nerves - A Self-Directed Learning Neuroanatomy Revision Resource - Eleni Patera (20668674) (2025)
The 'Anatomy of the Cranial Nerves' is a game-based learning neuroanatomy resource that is aimed to be used as a self-directed learning resource to revise the neuroanatomy of the cranial nerves. Even though this is a game-based learning resource, it does not use score points, as this is a resource that the user will use at their self-pace to improve their own knowledge and learning experience. Anatomy of the Cranial Nerves This neuroanatomy resource consists of four parts that aim to help the user at different stages of their learning of the neuroanatomy of the cranial nerves: Part 1: Crack the Cues, Identify the Cranial Nerve Part 1 aims to help the user recall the names of the 12 pairs of cranial nerves. There is a card for each cranial nerve, and each card consists of seven cues that will help the user identify the cranial nerve of interest. Part 2: Think Outside the Box - Describe the Cranial Nerve: Cues Are Off Limits Part 2 aims to challenge the user by asking them to describe the cranial nerve of interest without using the seven cues present on each card for each cranial nerve. Part 3: Master the Cranial Nerve, Dive into its Structural, Functional and Clinical Neuroanatomy Part 3 aims to test the user predominantly on their structural and functional knowledge of the cranial nerves. For each cranial nerve there are 5 questions, one of them is related to the clinical neuroanatomy of the cranial nerve of interest. Part 4: Boost your Knowledge - Explore the Cranial Nerves Involved in the Parasympathetic Nervous System Part 4 aims to test the user on their knowledge on the four cranial nerves that contain a parasympathetic functional component. It is recommended that users download this resource on a laptop to ensure the functionality of the navigation buttons. Accessibility: The intention is to adapt this resource in future to make it more accessible to those using assistive technology. In the meantime, please contact the author for more information via the email address below.